Methanotrophy Alleviates Nitrogen Constraint of Carbon Turnover by Rice Root-Associated Microbiomes - Cao, Weiwei; Cai, Yuanfeng; Bao, Zhihua; Wang, Shuwei; Yan, Xiaoyuan; Jia, Zhongjun (Frontiers in Microbiology, 2022)
The bioavailability of nitrogen constrains primary productivity, and ecosystem stoichiometry implies stimulation of N2-fixation in association with carbon sequestration in hotspots such as paddy soils. In this study, we show that N2 fixation was triggered by methane oxidation and the endophytic methanotrophs serve as microbial engines driving the turnover of carbon and nitrogen in rice roots. 15N2-stable isotope probing showed that N2-fixing activity was stimulated 160-fold by CH4 oxidation from 0.27 to 43.3 µmol N g-1 dry weight root biomass, and approximately 42.5% of the fixed N existed in the form of 15N-NH4+ through microbial mineralization. Nitrate amendment almost completely abolished N2 fixation. Ecophysiology flux measurement indicated that methane oxidation-induced N2 fixation contributed only 1.9% of total nitrogen, while methanotrophy-primed mineralization accounted for 21.7% of total nitrogen to facilitate root carbon turnover. DNA-based stable isotope probing further indicated that gammaproteobacterial Methylomonas-like methanotrophs dominated N2 fixation in CH4-consuming roots, while nitrate addition resulted in the shift of the active population to alphaproteobacterial Methylocystis-like methanotrophs. Co-occurring pattern analysis of active microbial community further suggested that a number of keystone taxa could have played a major role on nitrogen acquisition though root decomposition and N2 fixation to facilitate nutrients cycling while maintain soil productivity. This study thus highlights the importance of endophytic methanotrophs as both the biofilters of greenhouse gas methane and microbial engines of bioavailable nitrogen for rice growth.